2021
DOI: 10.1371/journal.pone.0259169
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism between mortality, population growth and ageing of the population in the European lower and upper middle income countries

Abstract: This paper analyses the effect of mortality rates (under-five and adult mortality) and population growth on the population ageing in a pooled sample of nine lower and upper middle European countries. Therefore, the main goal of this research is to investigate the ageing process of the population in the context of mortality mechanisms (under five and adult mortality) and of population growth in nine European LUMIs. The analysis is implemented in terms of Pooled least squares with cross-section fixed effects met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Punjab province exhibits a relatively higher level of accessibility to health services [ 46 ]; however, the spatial analysis conducted in this study reveals a concentration on high mortality rates, following a pattern known as H–H. The potential cause may be partially attributed to the escalating population growth in Punjab [ 72 , 73 ]; however, the study identified additional factors that predominately influence child mortality [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Punjab province exhibits a relatively higher level of accessibility to health services [ 46 ]; however, the spatial analysis conducted in this study reveals a concentration on high mortality rates, following a pattern known as H–H. The potential cause may be partially attributed to the escalating population growth in Punjab [ 72 , 73 ]; however, the study identified additional factors that predominately influence child mortality [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…By 2050, two thirds of older individuals with dementia will live in low‐ and middle‐income countries (LMICs). 1 As older adults in LMICs continue to experience longer survival rates and improved health‐care access 2 , 3 , 4 it is critical to understand the factors associated with cognitive decline and dementia risk to address the needs of these aging populations. While the bulk of research on Alzheimer's disease and related dementias (ADRD) comes from high‐income countries (i.e., the United States), cross‐national research offers a unique opportunity to understand the sociocultural factors associated with ADRD across individuals residing in the United States and LMICs such as Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…As the global demographic landscape transforms, the demand for formal care intensifies across countries. Middle-income nations, such as China, are facing significant pressures on their economic and physical foundations due to aging populations [1]. Presently, China possesses the world's largest elderly population [2].…”
Section: Introductionmentioning
confidence: 99%
“…The decline in family care is inevitable, necessitating increased formal care from society and rendering care facilities increasingly essential [6]. The restricted supply of care services and lagging construction of care facilities contrast with the burgeoning societal demand for care [7], a phenomenon more conspicuous in middle-income countries [1].…”
Section: Introductionmentioning
confidence: 99%